Analisis Faktor-Faktor Yang Mempengaruhi Keputusan Anggota Dalam Menyimpan Dana Di KSPPS Kota Semarang - Muhammad Fikri Aziz; Prabowo Yudo Jayanto (ECONBANK: Journal of Economics and Banking, 2021)
Islamic financial institutions in Indonesia are growing rapidly. However, the market-share of Islamic financial institutions are still far from conventional financial institutions. The purpose of this study was to determine effect of level of income, religiosity, culture, principle of profit sharing and quality of service to members saving decision at KSPPS in Semarang City. The population of this research are active members of KSPPS that registered in Dinas Koperasi dan Usaha Mikro Kota Semarang. The sample technique uses accidental sampling and the number of the sample of this research are 100 respondens. Primary data collection using questionnaire method. The data were analyzed using descriptive analysis and PLS-based Structural Equation Modelling (SEM) with SmartPLS 3.0 analysis tool. Result of this research showed that level of income, religiosity, culture, principle of profit sharing and quality of service has a significant positive effect on saving decision members at KSPPS in Semarang City.